Analisis ketebalan kortikal, ukuran sudut dan kepadatan trabekula tulang mandibula prajurit dan non prajurit ditinjau dari radiograf panoramik - Indra Gunawan; Suhardjo Sitam; Azhari Azhari; Krisnadi Setiawan (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: To analyze the cortical thickness, angular size and density of the mandibular bone trabeculae of soldiers and non-soldiers in terms of panoramic radiographs Material and Methods: This study is a comparative analytical descriptive study. The sample used was 65 panoramic radiographic data from soldiers and non-soldiers carried out at LADOKGI TNI AL R E Martadinata Jakarta. Results: Significant differences (p-value <0.05) in the calculation of the MCW value (Mandibular Cortical Width) of male soldiers compared to non-male soldiers (p-value 0.047) and FD FM (Fractal Dimension region superior foramen mentale) values 40-58 years compared to non-soldiers aged 40-58 years (p-value 0.027). Conclusion: There are differences in the size of the cortical thickness of the foramen mentale region (MCW) of the male group and in the value of the superior region of the mandibular foramen mentale (FD) region of the 40-58 years age group between soldiers and non-soldiers in terms of panoramic radiographs.